PELESTARIAN PERTANIAN ORGANIK BUAH NAGA: VALUASI EKONOMI DAN SIMULASI KEBIJAKAN - Kustiawati Ningsih; Halimatus Sakdiyah; Herman Felani; Rini Dwiastuti; Rosihan Asmara (Jurnal Agrisep)
Organic agriculture is the implementation of thesustainable agriculture concept promoted by the World Food Organization (WHO) since 1989. Later, this conceptbecomea global movement for sustainable agriculture (Suryana, 2005). In its development,organic farming of dragon fruit tendsto decrease its sustainability. The main contributing factors isnatural and environmental degradation phenomena. This study aims to analyze the NPV of corn farming activities, which incidentally are farming activities outside organic dragon fruit farming,by comparing tothe NPV of corn farming activities and organic dragon fruit farming NPV and conductingsensitivity analysis towardthe benefits and social costs of the dragon-fruit organic farming environment. The analytical method used is cost-benefit analysis. The results showed that there aredifferences in the value of benefits and costs between corn farming  and organic dragon fruitfarming. The difference between the benefits and costs, NPV and BCR between corn farming and organic dragon fruit farming occurred because organic dragon fruit farming considersthe value of social benefits and social costs, which includes elements ofbenefits and environmental costswhilecorn farming does not.Likewise, sensitivity analysis with a 10% increase in costs and a 5% decrease in benefits indicates that the NPV and BCR values are still positive. This shows that both types of farming found in the organic farming environment of dragon fruit are feasible to be developed so that they can maintain their existence for future generations and realize organic farming preservation of dragon fruit.